2017
DOI: 10.4068/cmj.2017.53.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Supraclavicular Lymph Node Excision Biopsy in Patients with Suspected Supraclavicular Lymph Node Metastasis of Lung Cancer: Experience in a Tertiary Hospital

Abstract: The aim of this study was to evaluate the usefulness and accuracy of supraclavicular lymph node excision biopsy in the diagnosis of suspected supraclavicular lymph node metastasis of lung cancer. A retrospective review was performed to evaluate patients with suspected supraclavicular lymph node metastasis of lung cancer who underwent supraclavicular lymph node excision biopsy from January 2011 to July 2014. Forty-six patients with suspected supraclavicular lymph node metastasis of lung cancer underwent supracl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
4
1
Order By: Relevance
“…Tuberculosis features prominently in our study (21 cases) as well as in the studies by Ashwini et al [ 23 ] and Tiwari et al [ 24 ]. Conversely, Lee et al [ 16 ] reported a higher incidence of metastatic lymphadenopathy (376 cases), which was not observed in our study. These discrepancies may stem from variations in geographical location or patient demographics.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Tuberculosis features prominently in our study (21 cases) as well as in the studies by Ashwini et al [ 23 ] and Tiwari et al [ 24 ]. Conversely, Lee et al [ 16 ] reported a higher incidence of metastatic lymphadenopathy (376 cases), which was not observed in our study. These discrepancies may stem from variations in geographical location or patient demographics.…”
Section: Discussioncontrasting
confidence: 99%
“…The reported accuracy of lymph node FNAC in existing literature ranges from 82% to 94.4% [ 15 ]. In the diagnosis of suspected lung cancer, excision biopsy of supraclavicular lymph nodes showed 100% sensitivity, 96.7 % specificity, 83.3 % positive predictive value, 100 percent negative predictive value, and 97.8 % diagnostic accuracy [ 16 ]. As FNAC is less invasive and has fewer complications, it can be a safe alternative to excision biopsy and should be recommended as a first-line investigation while excision biopsy as a second-line investigation only if the results of FNAC are not satisfactory [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence is the main cause of the death of patients with NSCLC, even for patients with clinical stage IA (10,11). Studies reveal that recurrence occurs mainly because NSCLC shows the features of "skip metastasis" and "micrometastasis" (12)(13)(14). The tumor cells in micrometastases are the source of postoperative recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, timely diagnosis and detection of lymph node metastasis in patients with lung cancer have important clinical significance for effective treatment and improvement of survival time of patients with lung cancer. However, the current diagnosis of lymph node metastasis in patients with lung cancer is mainly pathological examination, which is traumatic and may cause pain to the patient (14). The main non-invasive diagnostic method is enhanced CT and PDG-PET, however, they both involve radiation exposure that some patients are unwilling to accept (15).…”
Section: Discussionmentioning
confidence: 99%